Classification of Genes: Standardized Clinical Validity Assessment of Gene–Disease Associations Aids Diagnostic Exome Analysis and Reclassifications. Issue 5 (13th February 2017) - Smith, Erica D.; Radtke, Kelly; Rossi, Mari; Shinde, Deepali N.; Darabi, Sourat; El‐Khechen, Dima; Powis, Zöe; Helbig, Katherine; Waller, Kendra; Grange, Dorothy K.; Tang, Sha; Farwell Hagman, Kelly D.
Abstract : As diagnostic sequencing is increasingly employed, vast amounts of human genetic data are produced that need careful curation. We describe a standardized scoring system for accurately assessing the clinical validity of gene–disease relationships to interpret new research findings in a clinical context and increase the diagnostic rate. In turn, clinical validity scoring of gene–disease relationships can inform exome reporting and reanalysis, and gene selection for creation of diagnostic panels. ABSTRACT: Ascertaining a diagnosis through exome sequencing can provide potential benefits to patients, insurance companies, and the healthcare system. Yet, as diagnostic sequencing is increasingly employed, vast amounts of human genetic data are produced that need careful curation. We discuss methods for accurately assessing the clinical validity of gene–disease relationships to interpret new research findings in a clinical context and increase the diagnostic rate. The specifics of a gene–disease scoring system adapted for use in a clinical laboratory are described. In turn, clinical validity scoring of gene–disease relationships can inform exome reporting for the identification of new or the upgrade of previous, clinically relevant gene findings. Our retrospective analysis of all reclassification reports from the first 4 years of diagnostic exome sequencing showed that 78% were due to new gene–disease discoveries published in the literature. Among all exome positive/likely positive findings in characterized genes, 32% were in genetic etiologies that were discovered after 2010. Our data underscore the importance and benefits of active and up‐to‐date curation of a gene–disease database combined with critical clinical validity scoring and proactive reanalysis in the clinical genomics era. A video abstract of this article can be found athttps://bit.ly/2GrXa5w